2020
DOI: 10.7759/cureus.11376
|View full text |Cite
|
Sign up to set email alerts
|

Burning Mouth Syndrome Induced by Angiotensin-Converting Enzyme Inhibitors

Abstract: Burning mouth syndrome (BMS) is characterized as the sensation of burning in the tongue or any other area of the oral mucosa without a medical or dental cause. BMS's pathophysiology is poorly understood and may be caused by its association with various factors, particularly with antihypertensive or psychotropic medicines. Although BMS is a relatively common intraoral disorder in the dental field, emergency physicians rarely recognize it. We report a 53-year-old Japanese woman who presented to our ED with a thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
3
0
2
Order By: Relevance
“…A few case reports of scalded mouth syndrome have been reported with ACE Inhibitors, our case number 4 is one of them. A scalded sensation of the oral mucosa during the treatment with captopril or enalapril was initially reported [8].…”
Section: Effects Of Oral Hygiene On Overall Healthmentioning
confidence: 99%
“…A few case reports of scalded mouth syndrome have been reported with ACE Inhibitors, our case number 4 is one of them. A scalded sensation of the oral mucosa during the treatment with captopril or enalapril was initially reported [8].…”
Section: Effects Of Oral Hygiene On Overall Healthmentioning
confidence: 99%
“…(2) positivity at an oral fungal test and remission of the symptoms after treatment; and (3) dental, occlusal, and temporomandibular joint disorders inducing pain mimicking BMS symptomatology. As some authors have reported an association between BMS and the use of angiotensin-converting enzyme inhibitors (ACE inhibitors) [25,26], we referred the patients using ACE inhibitors to the cardiologists to replace this therapy. In 3 patients, the BMS symptoms remitted after 1 month of the replacement medication, and the patients were excluded from our study.…”
Section: Study Populationmentioning
confidence: 99%
“…Arminas Zizas 1 , Austėja Judickaitė 1 , Rūta Pribuišienė 2 1 Lietuvos sveikatos mokslų universiteto Medicinos akademijos Medicinos fakultetas, 2 Lietuvos sveikatos mokslų universitetas, Ausų, nosies ir gerklės ligų klinika 214 nergine reguliacija [7]. Prie etiologinių priskiriamas cirkadinio ritmo sutrikimas, galintis sukelti arba pabloginti esamą būklę [9]. Dėl mažo atliktų tyrimų kiekio, sudėtingos diagnostikos, etiologija ir patogenezė lieka neaiški, manoma, kad priežastis yra daugiaveiksnė [9].…”
Section: Degančios Burnos Sindromasunclassified
“…Prie etiologinių priskiriamas cirkadinio ritmo sutrikimas, galintis sukelti arba pabloginti esamą būklę [9]. Dėl mažo atliktų tyrimų kiekio, sudėtingos diagnostikos, etiologija ir patogenezė lieka neaiški, manoma, kad priežastis yra daugiaveiksnė [9]. Klinika.…”
Section: Degančios Burnos Sindromasunclassified